Freshwater fish diversity in three tributary streams in Serayu Basin, Central Java, Indonesia - suhestri suryaningsih; dian bhagawati; sri sukmaningrum; Sugiharto sugiharto; ayu ratna i gusti agung (Society for Indonesian Biodiversity, 2020)
Abstract. Suryaningsih S, Bhagawati D, Sukmaningrum S, Sugiharto, Puspitasari IGAAR. 2020. Freshwater fish diversity in three tributary streams in Serayu Basin, Central Java, Indonesia. Biodiversitas 21: 5811-5817. Determining the diversity of freshwater fish species in Central Java, Indonesia has been confounded by temporal and spatial limitations in past studies. The Serayu Basin is a large watershed in Central Java that is believed to have high freshwater fish diversity. We aimed to determine the diversity and community structure of freshwater fish species in three tributaries of the Serayu, elucidate the factors influencing this diversity, and determine the extent to which these tributaries contribute to the total freshwater fish species richness for southwest Central Java. We conducted gill net sampling from May to August 2018 on the Tulis, Mrawu, and Kali Sapi Rivers located at Banjanegara district Sampling followed a random group technique in upstream, midstream, and downstream river sections of each tributary. In total, we observed 21 freshwater fish species. Broadly, fish species diversity was relatively low in the study area, and water temperature and dissolved oxygen were important in maintaining fish diversity. These three tributaries house 27–46% of the freshwater fish species reported for southern Central Java.